Physicochemical Properties of New Plant Based Fiber from Lavender Stem. Issue 14 (28th October 2022) - Eyupoglu, Seyda; Merdan, Nigar
ABSTRACT: In this study, novel cellulosic fiber was obtained from Lavandula spp. (lavender) plant stem. The physico-chemical, morphological, thermal, and mechanical behaviors of lavender fibers were characterized. The energy dispersive X-ray analysis result of lavender shows that the fibers comprise of carbon (52.79%), oxygen (47.14%), and calcium (0.07%). Fourier transform-infrared analysis revealed that lavender fibers consist of cellulose and X-ray diffraction analysis indicates that lavender fiber has 65% crystallinity index. The thermogravimetric analysis shows that the lavender fibers are stable to 362.99°C. Young's modulus, tensile strength, and elongation at break of single fiber were obtained from the tensile test as 7.68–4.82 GPa, 226.65 MPa, and 2.94–4.69%, respectively.